Efecto de concentraciones de harina de bagazo de malta en las características bromatológicas y sensoriales de una galleta dulce - Loor Guerrero, María José (2026)
The objective of this research was to evaluate the nutritional and sensory effects of malt bagasse flour concentrations in a sweet biscuit. A Completely Randomized Design (CRD) was applied. The five treatments under study consisted of a percentage of Pilsen-type malt bagasse flour (25%, 20%, 15%, 10%), partially replacing wheat flour (control). The nutritional (pH, moisture, protein, hardness, and maximum bite force), microbiological (molds and yeasts), and organoleptic (color, odor, flavor, and texture) quality were evaluated by using an effective sensory acceptability test. In addition, the cost of the best formulation was determined. The results revealed that malt bagasse flour influenced on the nutritional parameters; However, only T5 (5% malt bagasse flour) showed optimal values for pH (6.46), moisture (8.29%), hardness (9.99 kg-f), protein (11.73%), and maximum bite force (8.06 kg/s), being statistically equal to the control. All treatments, including the control, complied with the permissible limits for molds and yeasts (1 x 10³ CFU/g) established by NTE INEN 2085:2005 for cookies. T5 (5% HBM) showed the highest acceptability in terms of color, aroma, flavor, and texture, being statistically equal to the control. Since T5 was the best treatment, it had a formulation cost of $3.80 for a production batch of 750 g of dough, yielding a total of 47.5 cookies of approximately 15 g each, with a unit cost of $0.08.